Polycentric monarchies : how did early modern Spain and Portugal achieve and maintain a global hegemony? - Cardim, Pedro (Sussex Academic Press, 2012)
Having succeeded in establishing themselves in Europe, Asia, Africa and the Americas, in the early 16th century Spain and Portugal became the first imperial powers on a worldwide scale. Between 1580 and 1640, when these two entities were united, they achieved an almost global hegemony, constituting the largest political force in Europe and abroad. Although they lost their political primacy in the seventeenth century, both monarchies survived and were able to enjoy a relative success until the early 19th century. The aim of this collection is to answer the question how and why their cultural an.